Apologies in Mandarin Chinese conversation: Lexical format and the reflexive construction of ‘apologizeables’ - Yu, Guodong; Raymond, Chase Wesley; Wu, Yaxin (Journal of pragmatics, 2025)
This paper uses the theory and methods of Conversation Analysis (CA) to explore the lexical design of apologies in naturally-occurring Mandarin conversation. We present three recurrent lexical formats used to issue apologies—(i) 不好意思 bùhǎoyìsī, (ii) 对不起 duìbùqǐ, and (iii) 抱歉/道歉 bàoqiàn/dàoqiàn—all of which are regularly translated into English as “(I'm) sorry” and/or “I apologize”. Rather than being used interchangeably, we argue that each of these formats is fitted to particular sorts of ‘apologizeables’, which are reflexively constructed as such through the issuing of the apology turn. The formats can therefore be arranged on a cline with regard to the gravity of the offense thereby indexed, with more ‘minimal’ offenses addressed with bùhǎoyìsī, comparatively graver apologizeables addressed with duìbùqǐ, and morally laden circumstances constructed with bàoqiàn and dàoqiàn. We also consider how lexical formats can be modulated through other aspects of turn design, like subject expression and adverbials, which likewise contribute to apology actions and their sequential relevancies. •We analyze three lexical formats for apologies in Mandarin conversation.•Selection of apology format reflexively constructs the offense addressed.•Lexical formats can be arranged on a cline of the severity of their offenses.